Destroyed by fire, preserved through time: crops and wood from a Late Bronze Age/Early Iron Age structure at Vila do Touro (Sabugal, Portugal) - Tereso, João Pedro; Vilaça, Raquel; Osório, Marcos; da Fonte, Leonardo; Seabra, Luís (Complutum, 2020)
Archaeological excavations at Vila do Touro uncovered a Late Bronze Age/Early Iron Age occupation at the top of a prominent hill. It consisted of a structure built with perishable materials, supported by postholes, and a small subcircular storage facility made of stone. Abundant carbonized plant remains were visible throughout the excavation area during the field work suggesting a fire occurred prior to the abandonment of the place, sometime in the 9th century BC. Archaeobotanical sampling allowed the recovery of abundant wood charcoal as well as charred fruits and seeds. Analyses showed structures were built mostly out of wood from deciduous oak, although pine was also used. Evidence for growth suppression in oak wood suggests direct human management of wood resources, which agrees with other evidences from northern Iberia. Moreover, the storage facility was used to keep cereals, mostly naked wheat and common millet, but also barley. These were stored fully processed and ready for consumption. Faba beans were also recovered, outside the small storage facility. Results are similar to sites in northeast Portugal and the Central Meseta but contrast with hillforts from Atlantic areas where hulled wheats are staple crops, suggesting a West-East trend also reflected in environmental and cultural features.